2022
DOI: 10.1155/2022/5501610
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Flexural Behavior of Prestressed Steel-Concrete Continuous Composite Beams Based on BP Neural Network

Abstract: Prestressed steel-concrete continuous composite beam (PCCB) is a kind of beam, which makes reinforced concrete slab and steel beam bear load and coordinate deformation through connectors such as studs. Prestressed steel-concrete continuous composite beam is a kind of transverse load-bearing composite member formed by prestressed technology on the basis of ordinary composite beam. Aiming at the flexural behavior of prestressed steel-concrete continuous composite beams, a three-dimensional finite element numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Han et al [26] used the BPNN to analyse the effect of different admixtures of waste fly ash on the compressive strength of high-performance concrete, and the results showed that the BPNN has high accuracy in predicting the compressive strength of waste fly ash concrete. Du Huanhuan et al [27] established a three-dimensional finite element numerical analysis model for the flexural performance of prestressed steelconcrete continuous composite beams and simulated the whole process of the test based on the BPNN. Cao et al [28] proposed a fully convolutional neural network to automatically identify and detect cracks by constructing a framework for learning concrete cracks and performing semantic segmentation to achieve crack identification.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [26] used the BPNN to analyse the effect of different admixtures of waste fly ash on the compressive strength of high-performance concrete, and the results showed that the BPNN has high accuracy in predicting the compressive strength of waste fly ash concrete. Du Huanhuan et al [27] established a three-dimensional finite element numerical analysis model for the flexural performance of prestressed steelconcrete continuous composite beams and simulated the whole process of the test based on the BPNN. Cao et al [28] proposed a fully convolutional neural network to automatically identify and detect cracks by constructing a framework for learning concrete cracks and performing semantic segmentation to achieve crack identification.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely adopted in the design and construction of various large-span bridges due to its high structural stiffness, lightweight properties, and reduced deflection [3][4][5][6]. Over the past several decades, researchers have conducted theoretical and experimental studies [7][8][9][10] to verify the excellent performance of the steel-concrete composite bridge deck system during the service life of bridge structures. Among various types of steel-concrete composite bridge deck systems, the orthotropic steel deck (OSD)-concrete structure has been extensively utilized in medium and large-span bridges due to its advantages such as lightweight design, high load-carrying capacity, and fast construction speed [11].…”
Section: Introductionmentioning
confidence: 99%